Internal and External Factors Affecting Profitability in Private Banking for the Period 2019-2023 - Lailatus Sa'adah; Putri Marsella Zalianti (CV. Proaksara Global Transeduka, 2025)
This research investigates how both internal and external elements impact the financial success of private banks that are publicly traded on the Indonesia Stock Exchange from 2019 to 2023. Factors within the banks such as Capital Adequacy Ratio (CAR) and Non-Performing Loans (NPL) will be analysed, along with external factors like inflation and the benchmark interest rate (BI Rate). Return on Assets (ROA) is a key indicator of banks' efficiency in terms of using their assets to make a profit. In this study, panel data regression analysis was used to analyse data from official financial reports. The results show that Capital Adequacy Ratio (CAR) has a positive impact on ROA, while Non-Performing Loans (NPL) have a negative impact. Interestingly, factors like inflation and the Bank Indonesia (BI) Rate do not seem to have a significant effect on ROA. This research distinguishes itself by focusing on how these variables interact within the unique environment of private banking in Indonesia. The study proposes various strategies to improve profitability, including better management of credit risks and capital adequacy.